Solitary Creations : 51 Artists out of De Stadshof Collection - Smolders, Frans; Reith, Liesbeth; Danchin, Laurent; ten Berge, Jos (Eindhoven : Collectie De Stadshof : Lecturis, 2014)
A.C.M. ; Alexandrine ; Azéma, Philippe ; Bos, Dirk ; Bossert, Herman ; Bros, Bonifaci ; Dammer, Aaltje ; Diakhaté, Adama ; Duhem, Paul ; Figueiredo, Luiz ; Fuldauer, Maurice ; Garnier, Jacky ; Glastra, Siebe Wiemer ; Grunenwaldt, Martha ; Hipkiss, Chris ; Hutting, Lies ; Jaber, El Majoub ; Jessberger, Tobias ; Jonkers, Bertus ; Kardol, Truus ; Kervezee, Jan ; Kijima, Saï ; Koczÿ, Rosemarie ; Koochaiki, Davood ; Lake, Reuben ; Lamy, Marc ; Langner, Hans ; Leonov, Pavel ; Lortet, Marie-Rose ; Manca, Bonaria ; Meurer, Markus ; Ndebele, Allina ; Nedjar, Michel ; Neervoort, Leo ; Nek Chand ; Pass, Donald ; Pomp, Jeroen; Saban, Ody ; Scholze, Hans ; Sefolosha, Christine ; Selhorst, Joseph ; Sluiter, Paula ; van Genk, Willem ; van Pagée, Ank ; Veenvliet, Henk ; Visser, Arie ; Wenzel, Roy ; Weree, Johnson ; Zalin, Karin ; Zemánková, Anna ; Zinelli, Carlo
boek